Innovation in Music Performance, Production, Technology and Business (Taylor & Francis, 2019)
Innovation in Music: Performance, Production, Technology and Business is an exciting collection comprising of cutting-edge articles on a range of topics, presented under the main themes of artistry, technology, production and industry. Each chapter is written by a leader in the field and contains insights and discoveries not yet shared. Innovation in Music covers new developments in standard practice of sound design, engineering and acoustics. It also reaches into areas of innovation, both in technology and business practice, even into cross-discipline areas. This book is the perfect companion for professionals and researchers alike with an interest in the Music industry.
English
Keywords: Music; business; innovation; music; performance; production; technology